ESTETIKA TARI LILIN BEPINGGAN PADA MASYARAKAT KAYU AGUNG KABUPATEN OGAN KOMERING ILIR PROPINSI SUMATERA SELATAN - Neni Krisniawati; Erlinda Erlinda; Susas Rita Loravianti (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT Lilin Bepinggan dance is an illustration of happiness originated from Miyah Malaman tradition. This tradition is usually done by the youngsters in Ramadan month especially in Lailatul Qadar night. The boy comes to his lover’s house by bringing the equipments of malaman such as candles, firecrackers, and fireworks. Yusrizal, as an artist and humanist, transforms this tradition into performancing art presented through Lilin Bepinggan dance. This dance has complex and aesthetic elements of dance that are interested to be studied further.The objective of this study is to understand the form and aesthetics of Lilin Bepinggan dance in Kayu Agung City, Ogan Komering Ilir District. This study utilized qualitative method in order to reveal and understand the aesthetics of Lilin Bepinggan dance. The data were obtained from (1) observation, (2) interview, and (3) documentation. The data were then verified and analyzed with the theories of form and aesthetics.The aesthetics element of Tari Lilin Bepinggan can be seen from physical reaction, harmony, and sensitive aspect of comprehension portrayed from the performance of Lilin Bepinggan dance that has been influenced by religious, cultural and social values. Keywords: Lilin Bepinggan dance, Aesthetics, Value, Social, Culture